Penerapan Metode TTW Berbantuan E-LKPD untuk Meningkatkan Keterampilan Menulis dan Hasil Belajar Materi Surat Pribadi - Agustin Susilowati (Ideguru: Jurnal Karya Ilmiah Guru, 2023)
This study aims at explaining the implementation of E-LKPD-assisted Think Talk Write (TTW) method to improve writing skills and learning outcomes in personal letter material for students in class XI IPA 2 at SMA Negeri 11 Yogyakarta for the 2021/2022 academic year. The research carried out was Classroom Action Research (CAR) based on Kemmis and McTaggart (1988), through the stages of planning, acting, observing, and reflecting. The E-LKPD-assisted TTW method was carried out by following stages 1) think; 2) talk; and 3) write. The results of the action showed that all indicators of writing skills increased in cycle 2. The mean of text content indicator increased by 3.42 points from 90.83 to 94.25 in cycle 2. The text organization indicator increased by 3.86 points from 88.58 to 92.44 in cycle 2. The vocabulary indicator increased by 3.19 points from 87.53 to 90.72 in cycle 2. The grammar indicator increased by 27.36 points from 58.97 to 86.33 in cycle 2. Meanwhile, the writing mechanism indicator increased by 5, 75 points from 86.06 to 91.81 in cycle 2. Data on learning outcomes showed that the average of student learning outcomes increased by 9 points from 75.92 to 84.92 in cycle 2. The percentage of the class mastery increased by19.45 points from 69,44%, to 88.89% in cycle 2. The percentage of class learning mastery by 19.45 points from 30.56%, to 11.11% in cycle 2.